2010
DOI: 10.1182/blood-2009-06-229369
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of chronic health conditions after hematopoietic cell transplantation: a report from the Bone Marrow Transplant Survivor Study

Abstract: Long-term survival is now an expected outcome after hematopoietic cell transplantation (HCT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
184
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 219 publications
(195 citation statements)
references
References 30 publications
(34 reference statements)
6
184
0
2
Order By: Relevance
“…2,16,17 This was not observed in a BMTSS study describing self-reported complications in mostly adult patients. 18 Child-specific adverse events like growth retardation might account for this difference. Abbreviation: BMD ¼ bone mineral density.…”
Section: Discussionmentioning
confidence: 99%
“…2,16,17 This was not observed in a BMTSS study describing self-reported complications in mostly adult patients. 18 Child-specific adverse events like growth retardation might account for this difference. Abbreviation: BMD ¼ bone mineral density.…”
Section: Discussionmentioning
confidence: 99%
“…of life compared with patients who undergo ASCT. 32 Several randomized studies 24,25,[33][34][35][36] comparing allogeneic stem cell transplantation using HLA-identical siblings after a myeloablative conditioning regimen with ASCT and chemotherapy have reported better outcomes after allogeneic transplantation, but they have also consistently shown a decreased relapse incidence after ASCT compared with conventional chemotherapy. However, to date no randomized study has demonstrated the superiority of allogeneic transplantation using an alternative donor (unrelated or cord blood) over ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] These problems include infections, second cancers, bone loss, and cardiovascular, pulmonary, renal, and endocrine dysfunction. 7,[10][11][12] Many factors contribute to the risks of late complications after HCT, including the antineoplastic treatments received before HCT, damage or adverse effects caused by the underlying disease, the chemotherapy and irradiation regimens used for conditioning before HCT, and medications such as corticosteroids, antibiotics, or calcineurin inhibitors used for years after HCT. Organ damage from infections or other complications during or after the transplantation process contribute to the increased risk of mortality.…”
Section: Medical Complications After Hctmentioning
confidence: 99%
“…Two thirds of adult long-term survivors have at least one chronic health condition, and approximately 20% have at least one severe or life-threatening condition. 7 Chronic graft-versus-host disease (GVHD) represents a unique late effect of allogeneic HCT that is not seen after other types of cancer treatment. This autoimmune-like complication can affect multiple organ systems and causes some of the most severe deficits in medical, symptom, and quality of life outcomes after HCT.…”
Section: Introductionmentioning
confidence: 99%